Diagnostic approach for cardiac involvement in sarcoidosis - Darlington, Pernilla; Gabrielsen, Anders; Cederlund, Kerstin; Kullberg, Susanna; Grunewald, Johan; Eklund, Anders; Sorensson, Peder (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2019)
Aims: Cardiac sarcoidosis (CS) is a potentially life-threatening condition. Early detection of CS is therefore important. The aim of this study was to eludicate the usefulness of different investigations in a subgroup of patients with sarcoidosis regarded as having an increased risk for cardiac involvement. Methods: 42 sarcoidosis patients, who had an abnormal resting electrocardiogram (ECG) and/or symptoms indicating possible cardiac involvement (i.e. palpitations, pre-syncope or syncope), were included in the study. They were identified in a consecutive manner among patients followed-up at outpatient clinics for respiratory disorders. Holter monitoring, exercise test, transthoracic echocardiogram (TTE), cardiovascular magnetic resonance (CMR) and analysis of N-terminal pro B-type natriuretic peptide (NT-pro-BNP) in serum were performed. Note, that the role of FDG-PET was not investigated in this study. Results: In the group with a pathologic ECG 11/25 (44%) were ultimately diagnosed with CS (all with pathologic CMR). However, in the group with only symptoms but a normal ECG just 1/17 got the diagnosis CS (p<0.05). This patient had a pathologic Holter monitoring. The risk for CS was increased if serum NT-pro-BNP was elevated (i.e. NT-pro-BNP>125 ng/L), sensitivity 78% (p<0.05), specificity 67%. By adding a pathologic ECG to an elevated NT-pro-BNP increased specificity to 93% and sensitivity remained at 78%. Conclusion: Our findings indicate that CMR should be performed at an early stage in sarcoidosis patients with an abnormal resting ECG. Holter monitoring and elevated levels of NT-pro-BNP may enhance the diagnostic accuracy whereas exercise testing and TTE in this study had less impact on the identification of CS.